10=-5m-m-2 would be solved easily
just simplify -5m and -m and that makes -6m
and add 2 to both sides which makes 12=-6m
divide each side by -6 and you get m=-2
however if you forgot to put parenthesis in the problem and it really looks like this:
10=-5m-(m-2)
then youd distribute the negative
10=-5m-m+2
add like terms
10=-6m+2
subtract 2 from both sides
8=-6m
divide by -6
m=8/-6
reduce
m= -4/3
2006-10-16 14:50:34
·
answer #1
·
answered by shark7777 3
·
0⤊
1⤋
Jason you might have got it wrong. in the first sentence you wrote 10=5m-m-2, it is actually NEGATIVE 5m. so yea -2 is the answer
2006-10-16 21:54:13
·
answer #2
·
answered by coolpowwow80 3
·
0⤊
0⤋
10 = -5m-m-2
10 + 2 = -5m-m-2 + 2
12 = -5m-m
12=-6m
-2 = m
2006-10-16 21:53:29
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
10=-5m-m-2
Combine like terms:
10=-6m-2
Add two:
12=-6m
Divide by -6:
m=-2
2006-10-16 21:48:58
·
answer #4
·
answered by Pascal 7
·
0⤊
1⤋
10= -5m-m-2
Step 1: add 2 to both sides
12= -5m-m
Step 2: combine terms
12= -6m
Step 3:
divide both sides by -6 to get " m" value
m= -2
2006-10-16 21:51:14
·
answer #5
·
answered by icycrissy27blue 5
·
0⤊
1⤋
10= -5m-m-2
12= -5m-m
12= -6m
-2= m
2006-10-16 21:55:31
·
answer #6
·
answered by idiotfoot11 2
·
0⤊
0⤋
break it down:
10+2=(-5m-1m)
12=-6m
12/-6=m
-2=m
so the answer is -2.
2006-10-16 21:50:07
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
combine like terms
10= -6m-2
add two on both sides
12=-6m
divide by -6
-2=m
2006-10-16 21:49:18
·
answer #8
·
answered by Anonymous
·
0⤊
1⤋
10+2=-6m
12=-6m
12/-6=m
-2=m
2006-10-16 21:52:52
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
10=-6m-2
12=-6m
m=-2
2006-10-16 21:56:02
·
answer #10
·
answered by Be my fan Please! 3
·
0⤊
0⤋